Distributed infinite‐horizon optimal control of continuous‐time linear systems over network. (9th November 2020) - Battilotti, Stefano; Cacace, Filippo; d'Angelo, Massimiliano
Abstract: This article deals with the distributed infinite‐horizon linear‐quadratic‐Gaussian optimal control problem for continuous‐time systems over networks. In particular, the feedback controller is composed of local control stations, which receive some measurement data from the plant process and regulates a portion of the input signal. We provide a solution when the nodes have information on the structural data of the whole network but takes local actions, and also when only local information on the network are available to the nodes. The proposed solution is arbitrarily close to the optimal centralized one (in terms of cost index) when a design parameter is set sufficiently large. Numerical simulation validate the theoretical results.